2000
DOI: 10.1046/j.1523-1747.2000.00878.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Responses of Peripheral Blood Mononuclear Cells to Staphylococcal Superantigen in Patients with Severe Atopic Dermatitis: A Role of T Cell Apoptosis

Abstract: Staphylococcus aureus colonization is an almost universal feature of atopic dermatitis. In order to investigate the role of staphylococcal enterotoxin B in the pathogenesis of atopic dermatitis, we assessed the correlation between clinical disease severity and proliferative response of peripheral blood mononuclear cells to staphylococcal enterotoxin B in patients with atopic dermatitis. Peripheral blood mononuclear cells from patients with mild atopic dermatitis showed significantly increased proliferative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
0
20
0
3
Order By: Relevance
“…On the other hand, Yoshino et al [29 ]assessed the correlation between clinical disease severity and proliferative response of PBMCs to SEB in vitro in AD. They found that PBMCs from their severe patients showed a markedly suppressed proliferative response to SEB.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Yoshino et al [29 ]assessed the correlation between clinical disease severity and proliferative response of PBMCs to SEB in vitro in AD. They found that PBMCs from their severe patients showed a markedly suppressed proliferative response to SEB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Akdis et al [9] reported that dysregulated apoptosis of effector cells plays a role in the pathogenesis of AD, with these mechanisms involving increased eosinophil survival, T-cell induced keratinocyte apoptosis and different T-cell lifespan in the peripheral blood and skin as a result of the intralesional cytokine microenvironment. Yoshino et al [10] also suggested that an infection of S. aureus, producing SEB, might play a role in the aggravation of AD by inducing apoptosis in T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Além disto, tem sido evidenciado que SEB induz uma supressão da resposta proliferativa nas PBMC de doentes atópicos, associada a uma diminuição na secreção de IFN-γ e aumento da produção de IL-4 (Yudate et al, 1996;Tanaka et al, 1996;Campbell, Kemp, 1997;Yoshino et al, 2000). A persistência do S. aureus na pele poderia contribuir com a inflamação da mesma, causando ativação contínua de células T e macrófagos.…”
Section: Papel Do Staphylococcus Aureus Na Daunclassified
“…Devido à grande variabilidade de doses utilizadas nos vários ensaios de proliferação encontrados na literatura, houve necessidade de realizar uma curva dose-resposta para as enterotoxinas A e B do S. aureus e escolha de uma dose adequada para realização do ensaio de proliferação (König et al, 1995;Tanaka et al, 1996;Yudate et al, 1996;Yoshino et al, 2000).…”
Section: Curva Dose-resposta Para Sea E Sebunclassified
See 1 more Smart Citation